Geology and hydrothermal vein system of the Jachymov (Joachimsthal) ore district - Ondrus,P.; Veselovsky,F.; Gabasova,A.; Hlousek,J.; Srein,V. (Journal of the Czech Geological Society, 2003)
This contribution provides a brief review of geology of the Krusnee hory Mts. (Erzgebirge) and specifically of the Jachymov (Joachimsthal) deposit. Main types of rocks in the Jachymov ore district and the role of tectonic processes are described. The position of the ore district is defined much like its tectonic borders. Geological factors controlling the mineralization (especially the so-called five-element mineralization) are summarized. Hydrothermal veins are divided into Morning and Midnight veins according to the classical historical speak of miners, and all vein clusters are listed. Vein hydrothermal five-element mineralization is chronologically divided into separate mineralization stages and their age is estimated.
Keywords: Geology; Krusne hory Mts.; Jachymov deposit; rocks; tectonics; mineralization